PELAKSANAAN PEMBELAJARAN MENYIMAK DI SD XAVERIUS DI BAWAH NAUNGAN YAYASAN XAVERIUS PALEMBANG - Katarina Retno Triwidayati (Jurnal PGSD Musi, 2018)
In language learning, four language skills (listening, speaking, reading, and writing) are essentially trained and developed. However, with various obstacles, listening skills are still underestimated. This research was conducted to find out the understanding of elementary school teachers under the auspices of Yayasan Xaverius Palembang related to the implementation of learning listening. This research was conducted in six schools under the auspices of Yayasan Xaverius Palembang using a qualitative research approach. The research involving 11 respondents of class I teachers showed the results of the teachers studied have not done the proper listening learning. Such inaccuracies relate to the listening teaching materials used, listening learning techniques, and evaluation of listening.